Analisis Pengelolaan Drainase Kota Kuala Tungkal Kabupaten Tanjung Jabung Barat - Nanik Sulastri (Jurnal Pembangunan Berkelanjutan, 2022)
This research has proposed to 1) To analyse sluice/puddle area control through drainage system in Kuala Tungkal City Tanjung Jabung Barat Regency 2) To have participation and community behaviour in drainage maintenance in Kuala Tungkal City Tanjung Jabung Barat Regency 3) To formulate government policy in Tanjung Jabung Barat in effort to manage drainage system Kuala Tungkal City. Primer data collection in this research conducted by surveying at field, interview and quitioner distribution for institution and community to get research goal. The primer data needed to cover existing condition of drainage system and community participation in sustainable drainage system management. The existing drainage system condition data received from observation and measurement at location, and community partitipation got from interviewing and quitioner list distribution to local community at Kula Tungkal City. From this research result showed 1) Parit 1, parit 2 and parit 3 as primer canal in secunder canal disposal through the sea. With function in drying, flowing and controlling water from sluice/puddle location at tungkal III subdistrict, Tungkal IV city and Patunas subdistrict. 2) Maintenance handed over to local community, the big portion becoming in regency government full responsibility. Institutional in community level only for temporary, including in subdistrict and district. No available regulation related with existing drainage management. 3) Responsibility arrangement firmly and coordinated with drainage system coordinator and related agency with BAPEMDAL as planner, PU agency as exsecutor and PPKTB to maintain and manage. Clear coordination with road users to avoid interference with canal draination.